Modeling of Cyber-Physical Systems - Holovatenko, Illya; Pysarenko, Andrii (Recent Developments in Automatic Control Systems, 2022)
The purpose is to review current research in the field of constructing cyber-physical systems. The structure of the chapter is as follows: a review of the most effective approaches and methods of constructing cyber-physical systems; using these methods-design cyber-physical-logistical system; perform the review of the obtained results and come up with a plan for further researches based on the reviewed methods. For validation of the designed system we came up with a live scenario from the logistical systems: the autonomous object delivers goods from one warehouse to another. We also will model obstacles along the way. The system should proactively react to this and recalculate the optimal path. This will lead to the timely delivery of goods to the destination.